Eficácia dos direitos fundamentais e a igualdade do direito ao trabalho entre homens e mulheres na empresa privada - Mendes, Dayane Aparecida Rodrigues (2024)
This scientific work establishes a relationship between the historical origin of the positivization of Fundamental Rights, originally to protect citizens from state abuses, and the effectiveness of these rights in private relations, especially when one of the subjects is a company. Analyzing the main Theories on the Horizontal Effectiveness of Fundamental Rights, in light of several Judgments issued by the Federal Supreme Court, it is found that in Brazil the Theory of Direct Effectiveness prevails as an instrument for the realization of Fundamental Rights, considering that the constitutional text of 1988 provides sufficient grounds for the realization of the Fundamental Rights declared therein. In this context, supported by material equality and the Principle of Human Dignity, the foundation of the Republic described in art. 1, III, and the principle of Economic Order provided for in art. 170, caput, both from the Citizen Constitution, while on the one hand it was found that Brazilian Constitutions prior to 1988 prohibited women from engaging in paid work, on the other hand, equality among employees of the same company is advocated. Thus, the study proposed that companies, based on the company's social function, can use affirmative actions to admit more women to their staff, as a form of historical compensation and, consequently, achieving full citizenship beyond the existential minimum, regardless of the law to that effect.